The effects of weightlifting shoes on squat kinematics - Fortenbaugh, D.; Sato, K.; Hitt, J. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Athletes may not always consider footwear when performing the barbell back squat during training. Several footwear companies have designed shoes claimed to enhance performance in weightlifting and powerlifting. The purpose of this study was to compare the kinematics of the barbell back squat wearing either running shoes (RS) or weightlifting shoes (WLS). Young, healthy active adult males (N=20) were filmed in the sagittal plane while performing barbell back squats for each shoe condition at an intensity of 60% of one repetition maximum (1RM). While a number of kinematic parameters were similar between conditions, the shank maintained a more vertical position and the bar and hip were displaced less when wearing WLS, suggesting a more erect trunk posture. WLS may make small changes that allow for a safer, more effective squat performance.